Writing and publishing a scientific research paper - Parija, Subhash Chandra; Kate, Vikram (Springer, 2018)
This book covers all essential aspects of writing scientific research articles, presenting eighteen carefully selected titles that offer essential, "must-know" content on how to write high-quality articles.